2022
DOI: 10.1111/mmi.14874
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus activates MLKL‐mediated host cellular necroptosis concomitantly with apoptosis to facilitate dissemination of viral progeny

Abstract: Reprogramming the host cellular environment is an obligatory facet of viral pathogens to foster their replication and perpetuation. One of such reprogramming events is the dynamic cross-talk between viruses and host cellular death signaling pathways.Rotaviruses (RVs) have been reported to develop multiple mechanisms to induce apoptotic programmed cell death for maximizing viral spread and pathogenicity. However, the importance of non-apoptotic programmed death events has remained elusive in context of RV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…For instance, dual inhibition of innate immunity and apoptosis by human cytomegalovirus protein UL37 × 1 enables efficient virus replication, but Caprine parainfluenza virus type 3N protein promotes viral replication via inducing apoptosis ( Ren et al, 2022 ). RIPK3-dependent necroptosis is induced and restricts viral replication in human astrocytes infected with Zika Virus ( Wen et al, 2021 ), while Rotavirus activates MLKL-mediated host cellular necroptosis concomitantly with apoptosis to facilitate dissemination of viral progeny ( Mukhopadhyay et al, 2022 ). Additionally, it was reported that AIM2 and NLRP3 inflammasome-mediated pyroptosis in EV-A71-infected neuronal cells restricts viral replication ( Hu et al, 2023 ; Yogarajah et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, dual inhibition of innate immunity and apoptosis by human cytomegalovirus protein UL37 × 1 enables efficient virus replication, but Caprine parainfluenza virus type 3N protein promotes viral replication via inducing apoptosis ( Ren et al, 2022 ). RIPK3-dependent necroptosis is induced and restricts viral replication in human astrocytes infected with Zika Virus ( Wen et al, 2021 ), while Rotavirus activates MLKL-mediated host cellular necroptosis concomitantly with apoptosis to facilitate dissemination of viral progeny ( Mukhopadhyay et al, 2022 ). Additionally, it was reported that AIM2 and NLRP3 inflammasome-mediated pyroptosis in EV-A71-infected neuronal cells restricts viral replication ( Hu et al, 2023 ; Yogarajah et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…ferroptosis inhibitors Ferrostatin-1 and Liproxstatin-1 resulted in reduced RV infection as estimated by expression of VP6 and viral titres confirming significant role of ferroptosis in modulating RV infection. Concurrently, RV has been shown to induce programmed cell death apoptosis and necroptosis during late hours of infection for effective dissemination of infectious progeny ( Bagchi et al., 2010 ; Chaïbi et al., 2005 ; Martin-Latil et al., 2007 ; Mukhopadhyay et al., 2022 ). The current study added ferroptosis to the repertoire of RV induced cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated form of MLKL oligomerizes and translocates to the plasma membrane of the cells infected by RV. This results in the loss of integrity of the host cell plasma membrane and the release of alarmin molecules such as HMGB1 which contribute to host cell death [202].…”
Section: Rna Viruses Induced Necroptosismentioning
confidence: 99%